Study on Performance of Large Megawatt Offshore Wind Turbine Couplings - Liu Jie; Wang Shuyong; Li Haijun; Jiang Hongwei (Jixie chuandong)
Considering the complex operating environment of offshore large megawatt wind turbines, a connecting rod coupling with metal elastic joints and parallel shaft holes is developed. The strength of its key components is checked, the overall finite element model of the connecting rod coupling is established, and the stress magnitude and distribution characteristics of each key component under rated (maximum) torque are analyzed.Based on the torque load sequence, combined with the coupling material S/N curve, and using finite element analysis software, the coupling fatigue life is obtained. Through stiffness tests, static and dynamic performance tests and dynamic balance tests, the overall axial, angular, and torsional stiffness are obtained, the slip torque is calibrated, and the torque transmission efficiency and dynamic balance level are given. The results show that the structural strength and life of the coupling meet the design requirements, and can achieve the expected slip torque effect; at the same time, the torque transmission efficiency can reach more than 99.93%, the dynamic balance level does not exceed G1.0, and the coupling performance can meet the requirements of large offshore wind turbines.